2012
DOI: 10.1155/2012/476979
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Neopterin and Inflammatory Activation in Chronic Kidney Disease

Abstract: Background. The serum levels of neopterin, a marker associated with cell-mediated immunity are elevated in chronic kidney disease (CKD). We evaluated serum neopterin levels and investigated its association with markers of inflammation in a cross-section of CKD subjects without known cardiovascular disease. Methods. Serum neopterin levels were measured in 118 patients with stage 3–5 CKD and 41 healthy subjects with normal kidney function (HC). Patients with known cardiovascular disease were excluded. We also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…15. We have shown previously that levels of IL-6 and hsCRP are associated with cardiovascular endpoints and all-cause mortality following kidney transplantation 4,16.…”
Section: Discussionmentioning
confidence: 95%
“…15. We have shown previously that levels of IL-6 and hsCRP are associated with cardiovascular endpoints and all-cause mortality following kidney transplantation 4,16.…”
Section: Discussionmentioning
confidence: 95%
“…The authors observed significantly elevated levels of soluble CX3CL1 in patients with carotid artery stenosis near occlusion (90%-99% stenosis) but similar levels among patients with moderate (50%-70% stenosis) and advanced (70%-90% stenosis) carotid artery disease [23] . Yadav et al assessed 62 healthy controls and 128 patients with stage III-V chronic kidney disease (CKD) [33,34] . The authors observed increased levels of soluble CX3CL1 in CKD subjects and a significant correlation between common carotid artery intima-media thickness and soluble CX3CL1 levels.…”
Section: Cx3cl1 and Atherosclerosis: Clinical Researchmentioning
confidence: 99%
“…Biopterin and neopterin concentrations in blood are high in patients with renal insufficiency. It is elevated and correlates with the severity of chronic kidney disease [17,18]. For that reason, we have excluded the patients with renal failure in our study.…”
Section: Discussionmentioning
confidence: 99%